Description Study of Student Nursing Perceptions on Online Learning During the Covid-19 Pandemic - Lembunai Tat Alberta; Dwi Adji Norontoko; Irfany Nurul Hamid (International Journal of Advanced Health Science and Technology, 2022)
The Covid-19 pandemic that is currently engulfing the world, including Indonesia, has changed the way people live, including education. The online learning process is one of the efforts made by the government in controlling the spread of Covid 19 among students. This study was conducted to explain students' perceptions of online learning, both aspects of the teaching and learning process, aspects of lecturers and infrastructure. The research sample was students majoring in nursing at the Sutomo Surabaya campus for the 2020/2021 academic year, totaling 510 people. Data was obtained online through Google Form, using a questionnaire, data were analyzed descriptively.   The results showed that students' perceptions of online learning were in a good category 37.8%, 61.4% sufficient, 0.8% less. The results of the research on student perceptions about online learning from the aspect of the teaching and learning process are in good category 22.35%, 76.87% sufficient, 0.78% less. Students' perceptions of online learning from the lecturer's perspective, good category 58.43%, 41.57% enough. Student perceptions of online learning from the aspect of infrastructure, good category 70.20%, 29.02% enough, 0.78% less. It is recommended to students improve their perception of online learning so that learning goals can be achieved to the maximum.